PEMBINAAN KEBUGARAN FISIK MELALUI PERMAINAN TRADISIONAL BAGI SISWA DI SDN 003 LOA JANAN ILIR KOTA SAMARINDA - Alif Tunru, Andi; Arifin, Nurdin; Subakti, Hani; Handayani, Lisa; Muhlis, Muhlis; Yuni Sahruni, Ade; Ramli, Musdalifah; Hidayat, Rachmat; Ilahi, Rahmat (Education and Talent Development Center of Indonesia, 2025)
Physical fitness is a crucial aspect in supporting the health, well-being, and academic achievement of students in schools. This issue is particularly relevant at SDN 003 Loa Janan Ilir, Samarinda City, especially following the pandemic period which caused a significant decline in students' physical activity. The problem statement and objective of this community service project are to explore how to develop the physical fitness of students at SDN 003 Loa Janan Ilir, Samarinda City, through the implementation of traditional game-based models. Differences in daily activities result in varying levels of students' physical fitness. Based on the calculation and analysis of research data, the following conclusions were drawn: 1) The physical fitness level of students at SDN 003 Loa Janan Ilir, Samarinda City, improved compared to the pre-test results, although still classified as moderate and low. 2) The implementation of physical fitness training based on traditional games successfully created a fun and interactive learning environment for the students. Traditional games were chosen because they are easily accessible, inexpensive, and engage all aspects of students' motor skills comprehensively. With this approach, students not only exercise but also learn through play. 3) The development of physical education teachers’ competencies at SDN 003 Loa Janan Ilir also showed progress. 4) Through training and mentoring provided, physical education teachers were able to master traditional game-based teaching methods more effectively and confidently. This community service activity at SDN 003 Loa Janan Ilir successfully introduced an innovative approach by applying traditional games as a medium for fostering students' physical fitness.